Space-temporal and extreme analysis of rain erosivity in the central-eastern region of the State of São Paulo, Brazil - Bolleli, Talyson; Santos, Bruno; Sanches, Rafael; Moreira, Rodrigo; Bourscheidt, Vandoir; Souza, Paulo Henrique de; Mauad, Frederico (Revista do Departamento de Geografia, 2023)
Soil degradation has become one of the most important environmental problems in the world due to rapid population growth, intensification of erosion processes and increased global warming. Seeking an efficient way of obtaining data for the calculation of Erosivity, this study aims to articulate the analysis of rainfall data with Geoprocessing and Remote Sensing techniques. Thirty-one pluviometric stations were used to acquire surface data, after the annual classifications, two years of extreme erosivity were selected, one rainy year and the other dry year. Among selected extreme years, a monthly classification of soil loss was performed for the twelve months of each representative year. Finally, the calculation of soil loss through RUSLE was applied, with the purpose of showing how the erosivity values in extreme years of rain and drought contribute to the process of soil loss in the study area. The results obtained show that the erosivity of the rain ranged from 4800 to 11100 Mj.mm.ha-1.h-1.year-1, with the observed average of 7950 Mj.mm.ha-1.h-1.year -1. RUSLE estimated average soil losses for the area of 8.2 Mg ha-1 yr-1 and 5.4 Mg ha-1 yr-1 for the years 1983 and 2014 respectively. Therefore, understanding the dynamics of Erosivity associated with soil losses can help in planning sustainable management and highlights the importance of minimizing water erosion.